The Effect of Green Bean to Increase Blood Hemoglobin Levels in Adolescents - Endang Widhiyastuti; Aulia Aulia; Sevy Astriana (Indonesian Journal of Global Health Research, 2022)
The country of Indonesia, is very rich in natural resources and has the potential for local food, namely nuts. green beans , one type of legume that is widely cultivated and used by the people of Indonesia. Green beans contain Fe as much as 3-9.7 mg/100 g. The high Fe content in green beans plays an important role in increasing blood hemoglobin levels. This study aims to determine whether green beans can be used as an alternative to increase blood hemoglobin levels. The research method is an experiment using a Pre-Experimental Design research conducted in June 2021 with the subject of the Karang Taruna Gema Putra members as many as 25 respondents with the criteria of respondents who are not menstruating. Data were collected by examining hemoglobin levels using the POCT method. Hypothesis testing is done by Paired t-Test. In this study, there were differences in hemoglobin levels between the groups before and after giving green bean powder drink with the results in the pre-treatment group an average of 13.87 g/dl and the post-treatment group having an average hemoglobin level of 13.87 g/dl. an average of 15.42 g/dl from the data, a significant increase of 1.55 g/dl. In this study, it was found that there was an increase in hemoglobin levels after giving green bean powder drink at Karang Taruna Gema Putra.